Biodiversity of soil cyanobacteria in the hyper‐arid Atacama Desert, Chile. Issue 4 (16th June 2014) - Patzelt, Dominik J.; Hodač, Ladislav; Friedl, Thomas; Pietrasiak, Nicole; Johansen, Jeffrey R.; Post, A.
<x xml:space="preserve">Abstract</x> The cyanobacterial diversity of soils of the Atacama Desert (Chile) was investigated using 16S rRNA gene cloning/sequencing directly from soil samples and 16S rRNA gene sequencing from unialgal cultures. Within the hyper‐arid Atacama Desert, one of the driest parts of the world, 10 sites with differing altitude and distance to the shore were sampled along a total air‐line distance (from south to north) of 1, 100 km. Filamentous cyanobacteria belonging to Nostocophycideae and Synechococcophycideae were present. Oscillatoriophycideae exhibited the highest species richness among the subclasses of cyanobacteria, and included mostly filamentous species along with some coccoids (e.g., Chroococcidiopsis). Thirty species‐level phylotypes could be recognized using a cut‐off of 99% 16S rRNA sequence similarity within the 22 genera defined at 97% 16S rRNA sequence similarity. Eight of the 30 taxa could be detected by both clonal and culture sequences. Five taxa were observed only in cultures, whereas the cloning approach revealed 17 additional taxa, which might be in the collection but unsequenced, hard‐to‐cultivate, or entirely unculturable species using standard cultivation media. The Atacama Desert soils have a high diversity of phylotypes, among which are likely both new genera and new species awaiting characterization and description.